Iraq : Considerations on Intergovernmental Fiscal Relations for the Constituent Assembly. (IMF Working Papers; Working Paper ;, 2005)
In preparing for the discussions of the Iraqi Constituent Assembly, IMF and World Bank staff and consultant experts presented to senior officials from the central and local governments in Iraq, including from Kurdistan, key options that might be relevant for the discussions. This paper reflects the thrust of the discussions, including the views on the options prepared by the Iraqi officials, and develops a short-term work plan for the benefit of the assembly.